The Government's Role in the Indonesian Rice Supply Chain - Galuh Octania (Center for Indonesian Policy Studies (CIPS), 2021)
In recent years, Indonesia has seen an opposite trend between rice supply and demand. It is predicted that rice consumption is likely to increase along with the growing population, yet rice production has declined. On top of that, the domestic rice distribution system's inefficiencies are regarded as one of the prominent reasons for high rice consumer prices in Indonesia. Despite Bulog's effort to ensure food security in the domestic supply chain, challenges still exist on upstream and downstream levels. Regulating the number of players in the distribution and processing chain is not an advisable option. In this policy paper, we recommend reforming two keys that can be considered: to redesign Bulog's role to ensure the domestic rice supply chain's efficacy and to ease import restrictions to encourage import competition to benefit from lower global rice prices.
Keywords: 330; rice; rice price; rice supply chain; bulog; farmer; middle man; rice miller; wholesalers; retailers; vietnam; philipines; malaysia; bernas; Statistics Indonesia; State-owned enterprise on food; Paddy; Dried Unmilled Rice; Price Ceiling; Rice Purchasing Price; Area Sampling Frame Method; Ministry of Agriculture; Ministry of Trade; National Food Authority; Vietnam Food Association